Disconnected: Exploring provisions for mother–child telephone contact in female prisons serving England and Wales - Booth, Natalie (Criminology & criminal justice, 2020)
Despite a growing body of international work describing the negative consequences of imprisonment for children and families, few studies have explored the accessibility and functionality of prison telephones. Mother-child contact has recurrently been identified as an important mechanism to alleviate and manage some of the emotional and practical adversities which accompany maternal imprisonment, and telephone contact has the potential to provide regular, perhaps even daily, contact for these separated family members. Responding to the knowledge gap, this article qualitatively explores the narratives of 15 mothers in prison with first-hand experience of using prison telephones to communicate with their children. Thematic data analysis revealed four critical obstacles and challenges with prison telephone facilities for Reconnecting in the first weeks, in the Cost of calling, in Telephoning privileges and Inconsistencies across prisons. Contrary to legal and policy guidelines, the findings illuminate how institutional barriers seriously affect mother-child communications, and recommendations are made.